La Poétique de l’intronisation dans les poèmes de Léopold Sédar Senghor - Mame Birame NDIAYE (Revue Hybrides)
Leopold Sedar Senghor will draw mainly from the depths of Mother Earth Africa, particularly in his childhood kingdom of the Sine, to feed his poetic creation. Thus, he will highlight one of the key events of his childhood in this inspiring place, namely the enthronement. In his poetry, he adopts a hybrid metric that seems to be specific to traditionalists, marked by negritude. Furthermore, he depicts the setting in which this celebration takes place, the singular rhythm that accompanies this coronation, as well as a certain poetic dimension that deepens this theme through various symbolic elements. In our article, we have analyzed this theme through six texts whose titles refer to the enthronement. To do so, we have drawn on our knowledge of testimonial literature and African history to explain the aristocratic influences to which the poet was exposed in his childhood, and which, consciously or unconsciously, are reflected in his writing.